Eosinophil-Associated Innate IL-17 Response Promotes Aspergillus fumigatus Lung Pathology - Malacco, Nathália Luísa Sousa de Oliveira; Rachid, Milene Alvarenga; Gurgel, Isabella Luisa da Silva; Moura, Tauany Rodrigues; Sucupira, Pedro Henrique Ferreira; Sousa, Lirlândia Pires de; Souza, Daniele da Glória de; Russo, Remo de Castro; Teixeira, Mauro Martins; Soriani, Frederico Marianetti (Frontiers in Cellular and Infection Microbiology, 2019)
Aspergillus fumigatus is a common widespread microorganism with environmental, biological and clinical relevance. After inhalation, swollen conidia can germinate, colonize and invade pulmonary tissues. Eosinophils have been described as key cells in A. fumigatus lung infection. However, their specific role in protecting or damaging lung tissue during A. fumigatus strains is poorly understood. Previously, it has been reported that eosinophils are able to produce IL-17 and mediate a Th17 innate response that protected mice from infection using Af293 and CEA10 strains. Here, we have developed a set of new experiments with the CEA17-derived A1163 strain of A. fumigatus. Using ΔdblGATA1 mice, we demonstrate that eosinophils produce IL-17 and are involved in control of neutrophil, macrophage and lymphocyte recruitment. We found that eosinophils also induce high levels of cytokines and chemokines, generating an intense inflammatory process. Eosinophils are responsible for increased pulmonary dysfunction and elevated lethality rates in mice. Curiously, fungal burden was not affected. To address the role of IL-17 signaling, pharmacological inhibition of this mediator in the airways with anti-IL-17 antibody was able to reduce inflammation in the airways and protect infected mice. In conclusion, our results demonstrate that eosinophils control IL-17-mediated response and contribute to lung pathology after A. fumigatus infection. Therefore, eosinophils may represent a potential target for controlling exacerbated inflammation and prevent tissue damage during this fungal infection.